On the manufacture of silver-BaCe0.5Zr0.3Y0.16Zn0.04O3−δ composites for hydrogen separation membranes. (22nd March 2015) - Ruiz-Trejo, Enrique; Zhou, Yuning; Brandon, Nigel P.
Abstract: Silver- BaCe0.5 Zr0.3 Y0.16 Zn0.04 O3−δ (Ag/BCZYZ) composites were investigated due to their potential application as hydrogen separation membranes, with emphasis on their fabrication and characterization. A precursor powder of BCZYZ was prepared via a wet chemical route and characterized by XRD, SEM and dilatometry. The precursor powder was coated with silver using Tollens reaction and then sintered under a variety of conditions. It was possible to obtain dense samples with a low level of non-percolating silver (2 vol%). Silver was present even if sintered at 1300 °C as it remained trapped in the ceramic matrix. The overall conductivity of a dense sample with 2 vol% of silver increased when compared to pure BCZYZ, and in particular the grain boundary resistance decreased considerably. A measurement of the open circuit voltage in fuel cell mode indicates the presence of mixed electronic-protonic conductivity in the composite. Highlights: An exploration of new alternative for the separation of hydrogen at 400–700 °C. First time manufacture of Ag and proton conductor (BCZYZ) composite. Higher bulk conductivity in composite than in pure BCZYZ. The high grain boundary resistance in BCZYZ is lowered with silver incorporation. Mixed electronic-protonic conductivity highlights potential for hydrogen separation.